(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article analyzes the issue of measurement in the series "Joseph and Zulayxo". For expressive reading of them, weight characteristics, measurement capabilities, coconuartic system have been studied. Instead, literature reacted to ideas.